Detrital zircon provenance of the Lower Cretaceous Duwon Formation based on LA-MC-ICPMS U–Pb ages and morphology in the Goheung area, southern Korea: A new supply mechanism of Early Cretaceous zircons. (December 2021) - Chae, Yong-Un; Ha, Sujin; Choi, Taejin; Kim, Cheong-Bin; Kim, Kyung Soo; Lim, Hyoun Soo
Abstract: Detrital zircons of five sandstones were analysed based on their laser ablation multi-collector inductively coupled plasma mass spectrometry uranium–lead (U–Pb) ages and their morphological features to reveal the provenance of the Lower Cretaceous Duwon Formation in Goheung, Korea. A total of 495 valid analytical points were obtained from zircon U–Pb dating, and in terms of age distribution, there were 361 Precambrian zircons (ca. 73%), nine Palaeozoic zircons (ca. 2%) and 125 Mesozoic zircons (ca. 25%). Except for 16 Cretaceous zircons, most were interpreted to be derived from the Yeongnam Massif and the southwestern Okcheon Basin located in the area to the northwest or west of the Duwon Formation. However, the Cretaceous zircons (ca. 127–118 Ma), which accounted for ~3% of all zircons, were formed during the magmatic quiescence in the Korean Peninsula, making it difficult to interpret their provenance at this time. This period coincided with active igneous activities in eastern China due to the low-angle subduction of the Palaeo-Pacific plate. In addition, westerlies were dominant due to the atmospheric general circulation. From morphological analysis of the zircons, Cretaceous zircons were smaller in size than those from other ages and generally had good sphericity and a euhedral shape. The overall evidence suggests the possibility that predominant westerly winds supplied Cretaceous zircons to the Korean Peninsula during explosive volcanic eruptions in eastern China during the Early Cretaceous. However, further studies are needed to clarify this hypothesis.